Study of Water Quality Changes in Balloran Dam lake using Canadian water quality indicator - جندي منلا عزيزه; عادل عوض; هيثم جناد (Latakia University Journal -Engineering Sciences Series, 2024)
This research aims to evaluate validity of Balloran Dam Lake for the purposes of drinking by using Water quality indices, to achieve this aim, Physical, Chemical and Bacterial measurements in four locations of the lake (S1, S2, S3, S4) were conducted periodically. The work continued to conduct tests for full hydrological cycle as of December (2021) until November (2022). The parameters measured are the following: Temperature Changes of water, PH- Value, Dissolved Oxygen, Biochemical Oxygen Demand, NO3‾, Total Suspended Solid, Turbidity, PO4‾3 and Fecal Coliform. Many of parameters have exceeded the allowable limits specifically. In accordance with the results that have been obtained, the lake has been classified according to the Canadian Water Quality index (CCME WQI) and was at the grade (D) in the sampling sites and the description was (Bad). By comparing the results of the quality index for the year 2022 with the results of the index for the year 2011, it appears that the decline in the quality of the lake’s water is the result of tourism and agricultural activity near the lake, and thus the lake’s water is not suitable for drinking and needs to be purified.